Biotic resistance by snails and fish to an exotic invasive aquatic plant - Ribas, Luiz Guilherme dos Santos; Cunha, Eduardo Ribeiro; Vitule, Jean Ricardo Simões; Mormul, Roger Paulo; Thomaz, Sidinei Magela; Padial, André Andrian (Freshwater biology, 2017)
Hydrilla verticillata (Hydrocharitaceae) is an exotic invasive macrophyte that has caused severe ecological and economic damage worldwide. H. verticillata has invaded the main channel of the river in the Upper Paraná River floodplain (Brazil), but it has not become established in floodplain lakes. Although some abiotic factors have been shown to affect the success of H. verticillata invasions, the role of biotic interactions remains unclear. Here, we set a laboratory experiment investigating how interactions with resident species may influence the success of H. verticillata invasions in floodplain lakes. Based on field observations, we selected three species that represent the most probable ecological interactions negatively impacting the early establishment of H. verticillata: a herbivorous fish (Moenkhausia forestii: Characidae) and herbivorous gastropods in the genus Pomacea (Ampullariidae), both natives, and an exotic shredder fish (Astronotus crassipinnis: Cichlidae). The individual and combined effects of these species on the early phase of H. verticillata establishment were evaluated. The native gastropod had the greatest effect on limiting plant growth due to herbivory, whereas the small native herbivorous fish mostly consumed H. verticillata leaves, and the non‐native shredder fish dislodged the plants from the sediment, preventing their establishment and increasing the number of free propagules (plant fragments) of previously rooted plants. The experimental treatment that combined all three species tended to reduce plant performance descriptors. Our results indicate that biotic resistance may play an important role in reducing the early establishment of H. verticillata in the lakes of this Neotropical floodplain. However, the disturbance caused by the exotic shredder fish may have an undesirable effect at larger scales because it stimulated the production of propagules that may spread to other connected aquatic ecosystems.